1999
DOI: 10.7547/87507315-89-2-81
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of heel spur surgery. A 10-year retrospective study

Abstract: A comparative retrospective study of 48 open heel spur surgeries and 20 endoscopic plantar fasciotomies was conducted involving 59 patients over a 10-year period. There was a significant reduction in heel pain at the time of follow-up (average, 3 years) for both groups. Overall, 85% of procedures were associated with patient satisfaction with the results, and patients said that they would recommend heel spur surgery for relief of severe heel pain in 94% of cases. Factors influencing the postoperative outcome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…These clinical findings are further supported by multiple studies that have demonstrated the removal of the plantar heel spur does not add to the success of the outcome in the surgical treatment of plantar heel pain. 13,[17][18][19] Calcification of the Achilles tendon insertion occurs primarily to the anterior and central portion of the tendon insertion. While local irritation of the spur may occur especially from shoe gear, the author's feel that primary source of pain occurs deep to the superficial tendon strands.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical findings are further supported by multiple studies that have demonstrated the removal of the plantar heel spur does not add to the success of the outcome in the surgical treatment of plantar heel pain. 13,[17][18][19] Calcification of the Achilles tendon insertion occurs primarily to the anterior and central portion of the tendon insertion. While local irritation of the spur may occur especially from shoe gear, the author's feel that primary source of pain occurs deep to the superficial tendon strands.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning surgical treatment, 5 retrospective case series, 44-48 which included 278 patients who experienced heel pain for an average duration of 14 months before surgery, showed that 75% to 95% of patients had long-term improvement as measured by various criteria. Up to 27% of patients still manifested significant pain, up to 20% had some activity restriction, and up to 12% had moderate pain that impaired foot function.…”
Section: Discussionmentioning
confidence: 99%
“…Die Erfolgsaussichten der klassischen offenen Fasciotomie wurden u. a. durch Vohra et al (1999) aufgezeigt. Sie erzielten in 85% gute Ergebnisse bei 48…”
Section: Diskussionunclassified